Preparation of Nanoemulsions with Low-Molecular-Weight Collagen Peptides from Sturgeon Fish Skin and Evaluation of Anti-Diabetic and Wound-Healing Effects in Mice - Nian-Ting Hou; Bing-Huei Chen (MDPI AG, 2023)
This study aims to isolate collagen peptides from waste sturgeon fish skin, and prepare nanoemulsions for studying their anti-diabetic and wound-healing effects in mice. Collagen peptides were extracted and purified by acetic acid with sonication, followed by two-stage hydrolysis with 0.1% pepsin and 5% flavourzyme, and ultrafiltration with 500 Da molecular weight (MW) cut-off dialysis membrane. Animal experiments were performed with collagen peptides obtained by pepsin hydrolysis (37 kDa) and pepsin plus flavourzyme hydrolysis (728 Da) as well as their nanoemulsions prepared at two different doses (100 and 300 mg/kg/day). The mean particle size of low-MW and low-dose nanoemulsion, low-MW and high-dose nanoemulsion, high-MW and low-dose nanoemulsion and high-MW and high-dose nanoemulsion was, respectively, 16.9, 15.3, 28.1 and 24.2 nm, the polydispersity index was 0.198, 0.215, 0.231 and 0.222 and zeta potential was −61.2, −63.0, −41.4 and −42.7 mV. These nanoemulsions were highly stable over a 90-day storage period (4 °C and 25 °C) and heating at 40-100 °C (0.5-2 h). Experiments in mice revealed that the low-MW and high-dose nanoemulsion was the most effective in decreasing fasting blood glucose (46.75%) and increasing wound-healing area (95.53%). Collectively, the sturgeon fish skin collagen peptide-based nanoemulsion is promising for development into a health food or wound-healing drug.